Cover Image. Issue 2 (18th January 2023) - Wang, Silin; Meng, Yuchen; Zhang, Yuchen; Huang, Fan; Teng, Rui; Lu, Yi; Li, Ang; Sun, Junyi; Pei, Dandan
Abstract : The cover image is based on the Research Article Influence of calcium‐based desensitizing toothpastes on the bonding performance of universal adhesive by Silin Wang et al., https://doi.org/10.1002/jemt.24280 .